The conceptual model of the structure and functional purpose of the geoinformation system for administrative and economic management of a regional airport - Prusov, Dmitry; Boyko, Olena (Geodesy and Cartography, 2022)
This article is devoted to the development of a conceptual model of the structure of the geoinformation system (GIS) for the administrative and economic management of regional airports, taking into account the requirements of world and national experience, international and national standards, modern technologies of geospatial data collection. The research is aimed at structuring all the facilities and objects of the airport complex and isolating components by location and function; development of a generalized scheme of directions for the use of administrative and business GIS at airports based on the analysis of world and domestic experience; establishing the need to use international and national standards of the “Geographic Information / Geomatics” series when creating an airport GIS; development of a generic scheme of the composition of the database of the Digital Single Topographic Base of the Airport, basic and profile geoinformation resources for the administrative and economic GIS; development of conceptual model of structure and functional purpose of GIS of administrative and economic management of the airport. The developed conceptual model reflects the main production processes and needs of airports, based on the database of the Digital Numeral Topographic Framework, is a complete and consistent model of the relationship between the administrative and economic needs of airports and the functionality of modern geoinformation systems for the efficient operation of objects, structures and facilities communications, analysis of the current state, monitoring and management decision-making.